Pengaruh Ukuran Perusahaan, Profitabilitas, Leverage, Likuiditas dan Sales Growth Terhadap Tax Avoidance - Yuliana Yuliana; Wuri Septi Handayani (Kajian Ekonomi dan Akuntansi Terapan, 2024)
The purpose of the study is to determine and analyze the effect of company size, profitability, leverage, liquidity and sales growth on tax avoidance in energy sector companies listed on the Indonesia Stock Exchange (BEI) for 2019-2023. In this study, a purposive sampling method was used, which obtained 45 companies. The data analysis used in this study is multiple linear regression analysis using SPSS software version 22 and Microsoft Excel 2019. The results of this study indicate that company size has a significant positive effect on tax avoidance, while leverage has a significant negative effect on avoidance, then profitability, liquidity and sales growth has no effect on tax avoidance.